Coagulation Profile in neonates with perinatal asphyxia - Jha, Ruchi; Verma, Neelam (International Journal of Contemporary Pediatrics, 2019)
Background: Perinatal Asphyxia refers to a condition during the first and second stage of labour in which impaired gas exchange leads to fetal acidosis, hypoxemia and hypercarbia. It accounts for about 23 per cent of the four million newborn deaths worldwide. Methods: To estimate the magnitude of coagulation derangement in babies who suffered birth asphyxia and compare it with non-asphyxiated controls. Results: There were 61.9% and 64 % males in both the groups outnumbering females suggesting that the health care seeking behavior for male children is more than for their female counterparts. Birth weight and mode of delivery are comparable in both the groups. PT and APTT were significantly higher in the asphyxiated babies than in their respective control group. It may be noted , however, that PT and APTT values were higher in the control group also, when compared with the reference values. This may indicate that the hemostatic mechanisms are already compromised in the newborns and perinatal asphyxia further augment the situation tilting it in favour of bleeding. Thrombocytopenia is observed in the asphyxiated group which may be due to placental insufficiency. Severe bleeding is significant in asphyxiated group as compared to the control. Conclusion: Dyscoagulation should be considered in all asphyxiated babies, and they may present with clinically significant bleeding, which may require fresh frozen plasma to restore and maintain their coagulation status.